Haplotype-phased genome and evolution of phytonutrient pathways of tetraploid blueberry. Issue 3 (31st January 2019) - Colle, Marivi; Leisner, Courtney P; Wai, Ching Man; Ou, Shujun; Bird, Kevin A; Wang, Jie; Wisecaver, Jennifer H; Yocca, Alan E; Alger, Elizabeth I; Tang, Haibao; Xiong, Zhiyong; Callow, Pete; et al.
Abstract: Background: Highbush blueberry ( Vaccinium corymbosum ) has long been consumed for its unique flavor and composition of health-promoting phytonutrients. However, breeding efforts to improve fruit quality in blueberry have been greatly hampered by the lack of adequate genomic resources and a limited understanding of the underlying genetics encoding key traits. The genome of highbush blueberry has been particularly challenging to assemble due, in large part, to its polyploid nature and genome size. Findings: Here, we present a chromosome-scale and haplotype-phased genome assembly of the cultivar "Draper, " which has the highest antioxidant levels among a diversity panel of 71 cultivars and 13 wild Vaccinium species. We leveraged this genome, combined with gene expression and metabolite data measured across fruit development, to identify candidate genes involved in the biosynthesis of important phytonutrients among other metabolites associated with superior fruit quality. Genome-wide analyses revealed that both polyploidy and tandem gene duplications modified various pathways involved in the biosynthesis of key phytonutrients. Furthermore, gene expression analyses hint at the presence of a spatial-temporal specific dominantly expressed subgenome including during fruit development. Conclusions: These findings and the reference genome will serve as a valuable resource to guide future genome-enabled breeding of important agronomic traits in highbush blueberry.